2013
DOI: 10.1158/1535-7163.mct-12-0357
|View full text |Cite
|
Sign up to set email alerts
|

HER2-Targeted Hybrid Peptide That Blocks HER2 Tyrosine Kinase Disintegrates Cancer Cell Membrane and Inhibits Tumor GrowthIn Vivo

Abstract: HER2 is a transmembrane oncoprotein encoded by the HER2/neu gene and is overexpressed in approximately 20% to 30% of breast cancers. We have recently designed a novel class of drug, the hybrid peptide, which is chemically synthesized and is composed of a target-binding peptide and a lytic peptide containing cationic-rich amino acid components that disintegrate the cell membrane, leading to cancer cell death via membrane lysis. In this study, we designed a HER2-binding peptide linked to this novel lytic peptide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Cytotoxic activity of EGFR-lytic or HER2-Lytic peptide was investigated in various normal cell lines. It was found that normal cells were only minimally susceptible to the novel hybrid peptides [12,13]. These encouraging preclinical data suggest that the tumor receptor-targeting hybrid peptides would be a new possible mechanism in cancer targeting therapy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Cytotoxic activity of EGFR-lytic or HER2-Lytic peptide was investigated in various normal cell lines. It was found that normal cells were only minimally susceptible to the novel hybrid peptides [12,13]. These encouraging preclinical data suggest that the tumor receptor-targeting hybrid peptides would be a new possible mechanism in cancer targeting therapy.…”
Section: Discussionmentioning
confidence: 93%
“…To improve tumor targeting effect, several peptide ligands of receptors expressed in tumor cells are conjugated with the Lytic peptide. Frequently-seen receptors are transferrin receptor (TfR) [11], human epidermal growth receptor 2 [12], epidermal growth factor receptor (EGFR) [13] and neuropilin-1 (NRP1) [14], etc. These hybird peptides have cytotoxicity and selectivity to cancer cells in both vitro and vivo.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, cellular uptake was enhanced leading to rapid entrance of nanoparticles into the tumor cells. In addition, the peptide-targeting moiety may have less immunogenicity and cytotoxicity than antibody-based ones because of its lower molecular weight [54]. Uptake of the peptide-nanoparticle conjugate in 4T1.2-neu breast cancer cells was appreciably higher than that of PEGylated INDs (Figure 5a).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is suggested that the inhibition of Hsp70 might exert effectively for cytotoxic activity via the inhibition of Hsp90 even in Hsp70-low expressing cancer cells. It has been reported that BT474 and MDA-MB-361 are Her2 high-expressing, and BT20 and MDA-MB-231 are Her2 low-expressing cancer cells, and that BT20, MDA-MB-361, and BT474 have mutations in PIK3CA , and only MDA-MB-231 has KRAS mutation among these cell lines [27, 28]. It has been also reported that BT474 is sensitive to both trastuzumab and lapatinib, and that MDA-MB-361 is sensitive to trastuzumab but resistant to lapatinib [29].…”
Section: Discussionmentioning
confidence: 99%